Experimental and numerical studies on superhigh strengthening sintered low alloy steels fabricated by metal injection molding) - Wan Sharuzi, Wan Harun (2013)
Metal injection molding (MIM) process is an advanced powder processing technique because of net shaping with shape complexity at low processing energy and 100 % material utilization. This study has been performed to clarify and to optimize the relationship between the mechanical properties and the microstructures for obtaining the superhigh strengthening sintered low alloy steels (Fe-Ni system) by using MIM process. The influence of nickel particle sizes, nickel content, and sintering conditions on the microstructure and mechanical properties of superhigh strengthened Fe-Ni steel compacts have been systematically investigated. As starting materials, the mixed elemental of carbonyl iron and water-atomized nickel powders were utilized. Tempered compact added 6 mass% fine nickel powder followed by sintering at 1250 °C for 1 hour showed superhigh strength of 2040 MPa with elongation of 8.1 %, which was the best properties among reported data in P/M low alloy steels so far. These excellent mechanical properties is due to the fine heterogeneous microstructure consisted of nickel rich phase surrounded by a networks of tempered martensitic structures. The mechanical properties of MIM compacts are highly dependent on two major factors; the porosity, and the microstructural morphology in the matrix. Both factors were cautiously considered in the present work. The porosity studies was carried out on 440C sintered steel, which was a high strength material with numerous pore contents. For the latter, the superhigh strengthened Fe-Ni steel compact, which is a primary alloy steel in this study was employed for microstructural studies on the matrix. Not only experimental work but also numerical simulation by finite element method was engaged to understand how these factors work. 440C steel compact has been purposely used as an example material to examine the pore factor. The utilization of 440C steel compact was due to homogeneous microstructure of matrix although contained many residual pores. The porosity study begins with experimental works, followed by numerical simulation for verification. The model demonstrated that tensile properties was enhanced at reduced pores and depreciated when the porosity was increased. Also, when mechanical properties of the compacts with similar porosity level is compared, the pore factor can be disregarded due to their minimum influences. However, the pores became a major factor when comparing compacts of different porosity levels. After the pore factor was successfully tested and evaluated, the effort had extended to the core focus of the present study. The effect of heterogeneous microstructure was treated in order to evaluate superhigh strengthened Fe-Ni steel compacts. Sintered density of all Fe-Ni steel compacts obtained in this study was 95-96 %, it means the porosity levels were about similar. Therefore, the pore factor has been simply omitted. The microstructure of all superhigh strengthened Fe-Ni steel compacts have been consistently structured by heterogeneous condition. The microstructural heterogeneity aspects of the compact were changed by the characteristics of Ni powder, such as particle size, shape, and content, which play important roles in the deformation behavior. A complex network of higher Ni region which firmly bounded by the lower Ni region (matrix region) has been comprehensively observed. The high ductility and high strength offered by the superhigh strengthened Fe-Ni steel compacts were probably also due to mechanically induced martensitic transformation that takes place during deformation. The material was initially metastable retained austenite, which was relatively ductile phase and the ductility was enhanced by the martensitic transformation-induced plasticity (TRIP) phenomenon. The high strength was due to the transformation of the soft austenite phase to the hard martensitic phase during the deformation as experimentally observed. In order to understand how the microstructure results these high mechanical properties, finite element modeling based on the spatial distribution obtained experimentally was developed. Some parameters were prepared to control heterogeneity in the representative volume element. The simulated results were compared to experimentally obtained behavior, and showed good agreements. These capabilities of successful simulation of the actual microstructure by FEM resulted possibility to identify and design an optimum microstructure theoretically for Fe-Ni system.